2022
DOI: 10.1016/j.xphs.2022.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Subvisible Particles Derived by Dropping Stress Enhance Anti-PEG Antibody Production and Clearance of PEGylated Proteins in Mice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The lipid-anchored PEG is incorporated to decrease macrophage-mediated clearance. More importantly, lipid-anchored PEG helps prevent particle aggregation and improve storage stability [483]. For cancer vaccine delivery, LNPs should be designed to protect mRNA from extracellular RNase degradation, and to deliver mRNA encoding antigens specifically to APCs, so to facilitate efficient antigen presentation, whilst not comprise mRNA translation [484].…”
Section: Rationale For Lipid Nanoparticles To Maximize Deliver Effici...mentioning
confidence: 99%
“…The lipid-anchored PEG is incorporated to decrease macrophage-mediated clearance. More importantly, lipid-anchored PEG helps prevent particle aggregation and improve storage stability [483]. For cancer vaccine delivery, LNPs should be designed to protect mRNA from extracellular RNase degradation, and to deliver mRNA encoding antigens specifically to APCs, so to facilitate efficient antigen presentation, whilst not comprise mRNA translation [484].…”
Section: Rationale For Lipid Nanoparticles To Maximize Deliver Effici...mentioning
confidence: 99%
“…The most commonly studied macromolecular polymer used to covalently bind to proteins is polyethylene glycol (PEG) by a process known as PEGylation, which introduces changes to the physicochemical properties of the protein molecule, thereby increasing its molecular size and weight, hydrophilicity and intermolecular interactions, in addition to changes in conformation. These changes introduced by the PEG help to decrease protein clearance while improving delivery to target sites and have been utilized to modify several commercial and clinically available peptide drugs [ 44 , 45 , 46 ], for which the efficacy and circulating half-life of PEGylated therapeutic proteins have been investigated [ 44 , 47 ]. Similar to PEG, human serum albumin (HSA) has been investigated and clinically tested as a binding module to improve the pharmacokinetics and pharmacodynamics of therapeutic proteins due to its low toxicity, high biocompatibility and apparently stable half-life within the human system [ 48 , 49 ].…”
Section: Elps Increase the Pharmacokinetic Properties Of Therapeutic ...mentioning
confidence: 99%
“…Discussion was divided on whether accuracy should be prioritized for SO droplets or protein particles. While protein aggregates are generally believed to be related to the immunogenicity of biopharmaceuticals, it was also reported that soluble and/or insoluble proteins accumulation around SO droplets may elicit undesired immune responses [14,28,29]. Continuously monitoring lot-to-lot consistency in protein particles and SO droplets would be crucial to ensure the quality and safety of prefilled syringe products.…”
Section: Building Streamlined Decision Treesmentioning
confidence: 99%